The application of Zhou Yi in financial market prediction. - Chan, Khai Heen. (2009)
Forecasting is an essential issue in financial markets. Among the modern forecasting tools, fundamental and technical analysis are extensively used. In this study, we will demonstrate how the ancient Chinese tool, Zhou Yi, can be a reliable forecasting method, especially in situations where information is lacking. Due to a lack of understanding, Zhou Yi is not widely used in financial markets. Hopefully, this illustration will give readers some understanding of this Chinese prediction method and establish the foundation for further research and application.